Guia de Preservação e Segurança da Biblioteca Nacional - Spinelli Junior, Jayme (2009)
This Guide of Preservation & Security of the National Library of Brazil to safeguard the holdings and the building aims to present guidelines, pathways and routes to procedures and attitudes towards questions of such nature, which are important and vital in an era full of uncertainties. As a base, we consider the knowledge acquired in the field of cultural property preservation and in the field of security policy adopted for bibliographical and documental holdings, researches and the buildings that stores them. The interdisciplinary character related to these fields of knowledge signals the educational improvement of the population as a whole and to our cultural memory. It aims at a changing in the role of man as a critic of nature, as a transforming agent of reality and of himself.